PERAN APARATUR KECAMATAN DALAM MEMBANGUN TATA PEMERINTAHAN YANG BAIK (Studi Pelayanan Publik Di Kecamatan Ilir Barat I Kota Palembang) - Ida Utami Dwikurniawati (Jurnal Pemerintahan dan Politik, 2019)
The role of the apparatus is very important in realizing good government, when the government policy on the implementation of regional autonomy is implemented. The basic principle of granting autonomy is based on the consideration that the region is more aware of the needs and standards of service for the community in its area, thus shortening the range of control services to the community. In the development of good governance there are several things that must be considered namely transparency, encourage community participation and encourage partnerships with private and community. In an increasingly complex life, rapid changes, higher interconnectedness, increasingly scarce natural resources, widening gaps and increasingly diminished earth carrying capacity, can not and should not be overcome with good governance. From the results of the discussion that the apparatus Kecamatan Ilir Barat I I Palembang city has not run its role well in an effort to provide excellent service to the community. Due to the impartiality of the apparatus and the disagreements that resulted in a lack of interest in participating in activities organized by the sub-district, and the lack of communication of the Sub-district Head with the community has resulted in the absence of community participation. Lack of such communication, causing the sub-district head to face various obstacles in establishing good relationships with their citizens. Less service to the community because the government Ilir Barat I of Palembang is not supported by professional apparatus who always try to give service to their society which can be realized through honest service, fast and free.Keywords: Role of Subdistrict Apparatus, Good Governance, Public Service.